GROWTH AND QUALITY OF SEEDLINGS OF VINHATICO (Platymenia foliolosa Benth.) IN RESPONSE TO THE MANURING WITH POTASSIUM AND SULFUR - Duarte, Marcie Lelis; Paiva, Haroldo Nogueira de; Alves, Marcela Oliveira; Freitas, Alex Ferreira de; Maia, Fabio Fernandes; Lima Goulart, Livia Mara [UNESP] (Centro Pesquisas Florestais, Ufsm, 2015)
The aim of this study was to evaluate the effect of potassium and sulfur on growth and quality of seedlings of Platymenia foliolosa Benth. (vinhatico), determining the best dose of these nutrients. An experiment was conducted using pots made of rigid polyethylene with a capacity of 1,5 dm(3) and a red and yellow Latosol as the substrate. Seven doses of potassium were used as substrates (0, 50, 100, 150, 200, 250 and 300 mg/dm(3)) combined with five levels of sulfur (0, 20, 40, 60 and 80 mg/dm(3)), which were applied in four applications: 0, 30, 60 and 90 days after the first thinning. After 150 days of sowing collected data of height, collar diameter, aerial part dry weight and root, and the relationships height/collar diameter, height/aerial part dry weight, aerial part dry weight/root dry weight and Dickson quality index (IQD). The addition of increasing doses of potassium to the substrate show significant (quadratic) for all variables, except for the ratio of aerial part height/collar diameter, the levels of sulfur showed no significant response to any of the characteristics evaluated in this experiment. There was an interaction between K and S to height of the aerial part in 'vinhatico' seedlings at 150 days after sowing. Based on these results, we recommend for seedlings of 'vinhatico' (Platymenia foliolosa) application of 175 mg / dm(3) K and 45 mg/dm 3 S parceled out evenly in four times at 0, 30th, 60th and 90 days after first thinning.
Keywords: native forest species; plant nutrition; plant propagation